Reseña de: Pérez González, Jordi: Sumptuary specialists and consumer elites in Rome’s world order - Mañas Romero, Irene (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2022)
Reseña de: Pérez González, Jordi: Sumptuary specialists and consumer elites in Rome’s world order, Universitat de Barcelona Editions, Collecció Instumenta 75, Barcelona 2021, 382 pp. ISBN: 978-84-9168-769-6.